2018
DOI: 10.1371/journal.pone.0198433
|View full text |Cite
|
Sign up to set email alerts
|

Non-fasting lipid profile determination in presumably healthy children: Impact on the assessment of lipid abnormalities

Abstract: ObjectiveDespite the common use of non-fasting measurements for lipid profile in children it remains unclear as to the extent non-fasting conditions have on laboratory results of lipids measurements. We aimed to assess the impact of non-fasting lipid profile on the occurrence of dyslipidemia in children.Materials and methodsBasic lipid profile including: total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C) and triglycerides (TG), as well as small, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…The results of the study revealed that the cut-off values among children in a non-fasting state, for the total cholesterol, are higher by about 30 mg/dL (upper cut-off value in fasting state was 200 mg/dl), while the TG concentration is 2.5-fold higher (upper cut-off value in fasting state for age 0-9 years was 100 mg/dl and for 10-19 years was 130 mg/dl) in comparison to determinations performed in a fasting state for similar age range groups [8]. What is more, the higher cut-off value was also different for the LDL-C concentration in comparison to that measured in a non-fasting state in the adult population.…”
Section: Discussionmentioning
confidence: 66%
“…The results of the study revealed that the cut-off values among children in a non-fasting state, for the total cholesterol, are higher by about 30 mg/dL (upper cut-off value in fasting state was 200 mg/dl), while the TG concentration is 2.5-fold higher (upper cut-off value in fasting state for age 0-9 years was 100 mg/dl and for 10-19 years was 130 mg/dl) in comparison to determinations performed in a fasting state for similar age range groups [8]. What is more, the higher cut-off value was also different for the LDL-C concentration in comparison to that measured in a non-fasting state in the adult population.…”
Section: Discussionmentioning
confidence: 66%
“…3 Triglycerides tend to have the largest variance between the two types of tests. 2 In children who are overweight and obese, there were no statistically significant differences between the fasting and nonfasting test results. 2 For nonfasting screens, the highest falsepositive rate is in triglycerides and the highest false-negative rate is in LDL-C. 2 If cholesterol levels are elevated with a nonfasting lipid panel, further evaluation should be completed with two separate fasting lipid panels at least 2 weeks apart.…”
Section: Fasting or Nonfasting Lipid Panel?mentioning
confidence: 91%
“…3,7,16 In 2011, the AAP endorsed the recommendation of the National Heart, Lung, and Blood Institute (NHLBI) that universal screening of children at age 9 to 11 years and again at age 17 to 21 years was warranted for early identification of dyslipidemia. 2,3,12,14,15,17 The timing of these laboratory tests is important as lipid levels are fairly stable from about Healthy Baby/Healthy Child age 2 years until a child reaches adolescence, but during puberty the levels of TC and LDL-C tend to decrease, and then begin rising again in the later teen years. 3 Screening in the mid-teen years may miss potentially affected children.…”
Section: Who Should Be Screened?mentioning
confidence: 99%
See 2 more Smart Citations